1990
DOI: 10.1152/jappl.1990.68.6.2280
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evidence for alveolar recruitment during inflation at high transpulmonary pressure

Abstract: The effect of continuous inflation of lungs at 30 cmH2O transpulmonary pressure (Ptp) on air-space size was assessed by chord length-frequency distribution analysis. Lungs from gerbils were excised, allowed to collapse freely, and inflated to 30 cmH2O Ptp in a humidified chamber kept at 37 degrees C. When the lungs appeared fully inflated with no observable pleural surface atelectasis, the left lung was occluded while the right was maintained at 30 cmH2O for 10 min longer and then occluded. During this time, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
32
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 0 publications
6
32
0
1
Order By: Relevance
“…Simultaneously, there is a decrease followed by an increase in alveolar airspace number per FOV with a similar trend reflected in the alveolar wall thickness. These results are best explained by recruitment of alveoli during high inflation pressures (similar to results presented by Lum and coworkers [18]), since there is an increase in alveoli number (Figure 4b), and mean alveoli airspace size is decreasing (Figure 4c). Simultaneously, the lung volume more than doubles during the change in inflation from 25 to 35 cm H 2 O pressure (Figure 4a).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Simultaneously, there is a decrease followed by an increase in alveolar airspace number per FOV with a similar trend reflected in the alveolar wall thickness. These results are best explained by recruitment of alveoli during high inflation pressures (similar to results presented by Lum and coworkers [18]), since there is an increase in alveoli number (Figure 4b), and mean alveoli airspace size is decreasing (Figure 4c). Simultaneously, the lung volume more than doubles during the change in inflation from 25 to 35 cm H 2 O pressure (Figure 4a).…”
Section: Discussionsupporting
confidence: 85%
“…Smaldone and coworkers observed recruitment of smaller alveoli (17), and in a later study Lum and colleagues, through histologic measurements of gerbil lungs fixed at various volumes, concluded that lung volume change was the result of alveolar recruitment/de-recruitment (18). Escolar and coworkers have also demonstrated that lung volume change is largely due to the number of alveoli, and they further postulated that the hysterisis between the inflation and deflation limb commonly observed in pressure-volume curves was the result of the number of open alveoli (19).…”
mentioning
confidence: 98%
“…The mean and SEM for nonparametric data (Lm) were calculated after a log transformation, which normalized the skewed data distribution (21). Subsequently, an exponential transformation was used to convert these values back to the linear scale.…”
Section: Discussionmentioning
confidence: 99%
“…The MLI and Lm differ by the mean thickness of the alveolar septa, but both are inversely proportional to the parenchymal surface/volume ratio (3). Both of these means are easy to measure from digital images, but measurement of individual airspace chords has the advantage of being able to provide statistics other than the mean (6,8,13). Although there often is a seductive intuition that has led many investigators (present author included) to implicitly and explicitly equate Lm with alveolar diameter, this is at best only a visual approximation, since the measurement chords traverse a complex structure of alveoli and ducts.…”
mentioning
confidence: 99%